Intelligent micro-navigation system for autonomous robots - Venugopalan Tharuvai Krishnaswamy (2013)
Autonomous vehicle or self-driving vehicle prototypes are being developed rapidly and are soon expected to become widespread. One can foresee a prospective future with ease of travel, fewer traffic collisions, congestions and higher travel speeds. Indoor autonomous vehicles possess applications such as firefighting, military combat, industrial-leak detection, etc.